Problem-Based Flipped Learning and Students’ Moral Judgment: The Mediating Role of Moral Sensitivity in Civic Education - Selly Rahmawati; Marzuki Marzuki; Victor Novianto; Sharifah Zannierah Syed Marzuki (Journal of Educational Science and Technology (EST), 2026)
Moral reasoning has become an increasingly important issue in higher education due to the growing complexity of ethical dilemmas in digital society. However, Civic Education instruction in higher education remains predominantly normative and content-oriented, with limited emphasis on reflective moral reasoning and ethical decision-making. Previous flipped learning studies have primarily focused on academic achievement, engagement, and critical thinking, while limited empirical research has examined the integration of Problem-Based Flipped Learning (PBFL) with moral development constructs, particularly Moral Sensitivity and Moral Judgment, within a structural mediation framework. Therefore, this study aimed to examine the structural relationships among PBFL, Moral Sensitivity, and Moral Judgment in Civic Education learning. This study employed a quantitative cross-sectional survey design with construct validation and structural modeling. The study involved 330 students enrolled in Civic Education courses in the Primary School Teacher Education Program. Moral Judgment was measured using contextual moral dilemma instruments developed from Kohlberg’s moral development theory and Rest’s Neo-Kohlbergian framework. Data were analyzed using covariance-based Structural Equation Modeling (CB-SEM) with jamovi version 2.6.44. The results demonstrated that PBFL had significant positive effects on Moral Sensitivity and Moral Judgment. Moral Sensitivity also significantly influenced Moral Judgment and partially mediated the relationship between PBFL and Moral Judgment. The structural model demonstrated satisfactory validity, reliability, and model fit indices. These findings indicate that PBFL effectively enhances students’ moral awareness, reflective reasoning, and ethical decision-making through authentic problem analysis, collaborative inquiry, and reflective deliberation. This study contributes theoretically by extending flipped learning research into the domain of moral development through the integration of flipped learning, Problem-Based Learning, and moral development theory within a mediation model. Practically, PBFL offers an innovative pedagogical approach for strengthening reflective and morally responsible citizenship in Civic Education learning.